Case-based reasoning in offshore well design - Mendes, JRP; Morooka, C. K.; Guilherme, I. R. (Elsevier B.V., 2003)
Petroleum well drilling is an expensive and risky operation. In this context, well design presents itself as a fundamental key to decrease costs and risks involved. Experience acquired by engineers is notably an important factor in good drilling design elaborations. Therefore, the loss of this knowledge may entail additional problems and costs. In this way, this work represents an initiative to model a petroleum well design case-based architecture. Tests with a prototype showed that the system built with this architecture may help in a well design and enable corporate knowledge preservation. (C) 2003 Elsevier B.V. B.V. All rights reserved.
Keywords: well design; drilling; case-based reasoning; fuzzy sets; genetic algorithms